2019
DOI: 10.1021/acs.orglett.9b02673
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Approach to the Metamorphosis of γ-Lactones to NH γ-Lactams via Reductive Cleavage and C–H Amidation

Abstract: A new approach has elaborated on the conversion of γ-lactones to the corresponding NH γ-lactams that can serve as γ-lactone bioisosteres. This approach consists of reductive C–O cleavage and an Ir-catalyzed C–H amidation, offering a powerful synthetic tool for accessing a wide range of valuable NH γ-lactam building blocks starting from γ-lactones. The synthetic utility was further demonstrated by the late-stage transformation of complex bioactive molecules and the asymmetric transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…C NMR (101 MHz, CDCl3) δ 146.6, 146.5, 146.0, 143.2, 137.3, 134.2, 126.4, 125.7, 125.5, 121.4, 119.8, 119.7, 114.5, 110.6, 106.1, 105.6, 31.4, 31.4. The data match with literature 22. …”
supporting
confidence: 87%
See 1 more Smart Citation
“…C NMR (101 MHz, CDCl3) δ 146.6, 146.5, 146.0, 143.2, 137.3, 134.2, 126.4, 125.7, 125.5, 121.4, 119.8, 119.7, 114.5, 110.6, 106.1, 105.6, 31.4, 31.4. The data match with literature 22. …”
supporting
confidence: 87%
“…The data match with literature. 22 2-(1-Methyl-1H-benzo[d]imidazol-2-yl)propan-2-ol (3c). Protocol A was followed, 1-Methyl-2-undecyl-1H-benzo[d]imidazole (1m) (34.8 mg, 0.2 mmol) was employed as the substrate.…”
Section: -Bromomentioning
confidence: 99%
“…We also developed a synthetic approach to convert lactones to the corresponding NH-lactams with interesting biological activities. 35 We next turned our attention to aryl C(sp 2 )−H bond amidation by utilizing the Cp*Ir(κ 2 -LX) catalyst system. In fact, Driver 36 and Falck 37 reported that processes using aryl azides and hydroxylamines with dirhodium(II) catalysts proceed via electrocyclization and electrophilic aromatic substitution (S E Ar), respectively.…”
Section: Co and Ru Catalysismentioning
confidence: 99%
“…This amidation protocol was highly effective even with more complex substrates that possess multiple competing C–H bonds, and it was well-suited for derivatizing naturally occurring carboxylic acids at the late synthetic stage. We also developed a synthetic approach to convert lactones to the corresponding NH -lactams with interesting biological activities …”
Section: C–n Bond Formation: Outer-sphere Pathwaymentioning
confidence: 99%
“…The carboxyl group of 2 a could be easily transformed to acyl chloride and further to ester and amide, providing 6 a in 76 % yield with 94 % ee and 7 a in 66 % yield with 94 % ee . In particular, ring opening of the chiral lactone 6 a could be achieved by subsequent hydrogenation of carbon‐carbon double bond and reductive cleavage of C−O bond with Pd/C, [37] giving monoester 8 a in 60 % yield with 92 % ee . In the previous report, monoester 8 a was synthesized by PLE‐catalyzed kinetic resolution from the prochiral diester for up to 7 days with only 36 % ee [38] .…”
Section: Resultsmentioning
confidence: 99%